ANALYSIS OF HUMAN RESOURCE DEVELOPMENT AND ITS RELATION TO EMPLOYEE JOB SATISFACTION ON PT. BANK MUAMALAT KC PADANGSIDIMPUAN - ayulina ayulina; nofinawati nofinawati; indah sari (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The background of the problem in this research is the lack of human resource development and its relation to employee job satisfaction at PT. Bank Muamalat KC Padangsidimpuan. The results of observations of various problems that have occurred require complex thinking, this needs to be solved immediately, especially the problem of HR at PT. Bank Muamalat KC Padangsidimpuan. Some employees occupy fields of work that are not in accordance with their disciplinary background, besides that there are also complaints that there are difficulties in carrying out their duties as a result of decreased morale. So that the formulation of the problem in this study is whether there is an influence of the program and HR development factors on employee job satisfaction. Then the purpose of this study was to determine the human resource development program and what factors affect employee job satisfaction at PT. Bank Muamalat KC Padangsidimpuan. The theory presented in this study is the theory of human resource development, objectives, principles of human resource development, factors that influence human resource development, training theory, career development theory, compensation theory, job satisfaction theory and factors that influence job satisfaction. work. The research method used in this study is a qualitative method, with the research location at PT. Bank Muamalat KC Padangsidimpuan with data collection techniques including observation, interviews, and documentation which aims to find out how Human Resource Development and its relation to employee job satisfaction at PT. Bank Muamalat KC Padangsidimpuan The results of this study are, based on the discussion that has been presented, the results of the research show that the development of human resources in each company is very important to note because one of the factors that influence the development of human resources at PT. Bank Muamalat KC Padansgsidimpuan will affect the level of progress of the company and will also affect the employees themselves in order to improve the quality and quantity of employee work so that employees will feel satisfied with the work results and positions or positions of employees at PT. Bank Muamalat KC Padangsidimpuan.